Carnitine O-octanoyltransferase (CROT) deficiency in mice leads to an increase of omega-3 fatty acids - Okui, Takehito; Kuraoka, Shiori; Iwashita, Masaya; Itagawa, Rei; Kasai, Taku; Aikawa, Masanori; Singh, Sasha A.; Aikawa, Elena (Frontiers in Molecular Biosciences, 2024)
Introduction: Carnitine O-octanoyltransferase (CROT) is a well-established peroxisomal enzyme involved in liver fatty acid oxidation, but less is known about its recently discovered role in promoting vascular calcification, and whether CROT-dependent liver metabolism contributes to the latter. To date, CROT function in the context of calcification potential has been conducted in the dyslipidemic low-density lipoprotein receptor-deficient (Ldlr−/−) mice. Objectives: To differentiate peroxisome and CROT-dependent lipid biology from that of lipoprotein-mediated lipid biology, we therefore conducted a metabolomic analysis of the liver and plasma of normolipidemic CROT-deficient (Crot−/−) mice. Methods: We performed LC-MS-based metabolomics on liver and plasma derived from Crot−/− and Crot +/− mice and sibling Crot+/+ mice, using a dual-phase metabolite extraction protocol, and multiple LC-MS acquisition strategies. Results: We identified between 79 to 453 annotated metabolites from annotated metabolites from liver samples, and 117 to 424 annotated metabolites from plasma samples. Through differential abundance analysis, we determined that omega-3 fatty acids such as EPA, DPA, and DHA were higher in the liver of Crot−/− and Crot +/− mice than Crot+/+ mice. EPA were higher in plasma of Crot−/− mice than Crot+/+ mice. We also determined that the anti-inflammatory dicarboxylic acids, tetradecanedioic acid and azelaic acid, were higher in the plasma of CROT-deficient mice. Conclusion: Our study associated genetic CROT deletion with increased levels of anti-inflammatory molecules in mouse liver and plasma. These results suggest a potential mechanism for anti-calcification effects of CROT suppression and the potential use of omega-3 fatty acids as biomarkers for future CROT inhibition therapies.